Epithelial cell invasion by salmonella typhimurium induces modulation of genes controlled by aryl hydrocarbon receptor signaling and involved in extracellular matrix biogenesis - Anne-Marie Chaussé; Sylvie M. Roche; Marco Moroldo; Christelle Hennequet-Antier; Sébastien Holbert; Florent Kempf; Emilie Barilleau; Jérome Trotereau; Philippe Velge (Virulence)
Salmonella is the only bacterium able to enter a host cell by the two known mechanisms: trigger and zipper. The trigger mechanism relies on the injection of bacterial effectors into the host cell through the Salmonella type III secretion system 1. In the zipper mechanism, mediated by the invasins Rck and PagN, the bacterium takes advantage of a cellular receptor for invasion. This study describes the transcriptomic reprogramming of the IEC-6 intestinal epithelial cell line to Salmonella Typhimurium strains that invaded cells by a trigger, a zipper, or both mechanisms. Using S. Typhimurium strains invalidated for one or other entry mechanism, we have shown that IEC-6 cells could support both entries. Comparison of the gene expression profiles of exposed cells showed that irrespective of the mechanism used for entry, the transcriptomic reprogramming of the cell was nearly the same. On the other hand, when gene expression was compared between cells unexposed or exposed to the bacterium, the transcriptomic reprogramming of exposed cells was significantly different. It is particularly interesting to note the modulation of expression of numerous target genes of the aryl hydrocarbon receptor showing that this transcription factor was activated by S. Typhimurium infection. Numerous genes associated with the extracellular matrix were also modified. This was confirmed at the protein level by western-blotting showing a dramatic modification in some extracellular matrix proteins. Analysis of a selected set of modulated genes showed that the expression of the majority of these genes was modulated during the intracellular life of S. Typhimurium.